Escalation of Commitment in Internationalization Processes The Role of Bounded Rationality in the Uppsala Model - Röber, Björn (MIR Series in International Business, 2018)
This unique book on international business presents a critical review of the role of bounded rationality in internationalization process (IP) research. Corporate internationalization processes have been a subject of scientific debate for several decades. However, it is questionable whether behavioral research insights are sufficiently acknowledged in this academic discipline. Against this backdrop, the author critically assesses the behavioral assumptions of the Uppsala Model, which is commonly considered to be the pivotal approach in internationalization process research.